Familial amyotrophic lateral sclerosis-linked SOD1 mutants perturb fast axonal transport to reduce axonal mitochondria content. - MCLOUGHLIN, DECLAN (Oxford University Press, 2007)
Amyotrophic lateral sclerosis (ALS) is a late-onset neurological disorder characterized by death of motoneurons. Mutations in Cu/Zn superoxide dismutase-1 (SOD1) cause familial ALS but the mechanisms whereby they induce disease are not fully understood. Here, we use time-lapse microscopy to monitor for the first time the effect of mutant SOD1 on fast axonal transport (FAT) of bona fide cargoes in living neurons. We analyzed FAT of mitochondria that are a known target for damage by mutant SOD1 and also of membrane-bound organelles (MBOs) using EGFP-tagged amyloid precursor protein as a marker. We studied FAT in motor neurons derived from SOD1G93A transgenic mice that are a model of ALS and also in cortical neurons transfected with SOD1G93A and three further ALS-associated SOD1 mutants. We find that mutant SOD1 damages transport of both mitochondria and MBOs, and that the precise details of this damage are cargo-specific. Thus, mutant SOD1 reduces transport of MBOs in both anterograde and retrograde directions, whereas mitochondrial transport is selectively reduced in the anterograde direction. Analyses of the characteristics of mitochondrial FAT revealed that reduced anterograde movement involved defects in anterograde motor function. The selective inhibition of anterograde mitochondrial FAT enhanced their net retrograde movement to deplete mitochondria in axons. Mitochondria in mutant SOD1 expressing cells also displayed features of damage. Together, such changes to mitochondrial function and distribution are likely to compromise axonal function. These alterations represent some of the earliest pathological features so far reported in neurons of mutant SOD1 transgenic mice.
PUBLISHED
Keywords: Psychiatry